Math Path: Encouraging Female Students in Mathematics Through Project-Based Learning. Issue 4 (21st April 2018) - Evans, Riley; Friedman, Jane; McGrath, Lynn; Myers, Perla; Ruiz, Amanda
Abstract: Although the number of bachelor's degrees in the U.S. awarded to women has gone up, engagement of women in science, technology, engineering, and mathematics (STEM) continues to be low. This paper presents a project-based learning program, informed by education research best practices, designed to provide research experiences to female students early in their academic careers. Mentored by female faculty, students voluntarily collaborate on extracurricular mathematical research projects that they select together based on their interests and passions. They then prepare and share their work at an undergraduate research celebration event at the university and at other conferences.